Effect of Placement Based on Expertise and Work Experience on Employee Work Productivity In PDAM Tirtanadi Branch Tuasan - Desy Ratnasari Marbun (Enrichment : Journal of Management, 2019)
One of the assets of a company engaged in the provision of clean water infrastructure quality is the Regional Water Company (PDAM) in general taps have a mission which is not the same with other companies. This is caused because a local company taps not only profit-oriented (propit) alone, but the leaders and employees of taps should give a good productivity for the company.Based on the data processing is done the determination test, the coefficient of determination Adjusted R Squareamounted to 0,629. This suggests that the ability of the placement variable (X1) and experience (X2) describes the impact on work productivity variable variable (Y) on taps Tirtanadi Tuasan Branch of 62.9%. While the rest of 37.1% is the influence of other variables not examined in this study. Based on t test was obtained that reject Ho and accept H1 for placement variable (X1) and experience (X2). Thus, the partial placement and experience a positive effect with significant influence on the level of labor productivity in PDAM Branch Tirtanadi Tuasan. Based on the results of F test, obtained results of the test requirements of the effect that if F count> F table is 31.269> 3.32.